A comprehensive framework to enhance numerical simulations in the spectral-element code Nek5000 - Massaro, D.; Peplinski, A.; Stanly, R.; Mirzareza, S.; Lupi, V.; Mukha, T.; Schlatter, P. (Computer Physics Communications, 2024)
A framework is presented for the spectral-element code Nek5000, which has been, and still is, widely used in the computational fluid dynamics (CFD) community to perform high-fidelity numerical simulations of transitional and high Reynolds number flows. Despite the widespread usage, there is a deficiency in having a comprehensive set of tools specifically designed for conducting simulations using Nek5000. To address this issue, we have created a unique framework that allows, inter alia, to perform stability analysis and compute statistics of a turbulent flow. The framework encapsulates modules that provide tools, run-time parameters and memory structures, defining interfaces and performing different tasks. First, the framework architecture is described, showing its non-intrusive approach. Then, the modules are presented, explaining the main tools that have been implemented and describing some of the test cases. The code is open-source and available online, with proper documentation, to-run instructions and related examples.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Computational fluid dynamics; Numerical toolbox; Stability analysis; Statistical analysis